1994
DOI: 10.1021/ja00089a019
|View full text |Cite
|
Sign up to set email alerts
|

Steric Control of secondary, solid-state architecture in 1:1 complexes of melamines and barbiturates that crystallize as crinkled tapes

Abstract: This paper describes the single-crystal X-ray structures of four 1 : 1 complexes between N,iV'-di(tett-butyl)-melamine and 5,5-disubstituted barbituric acids (substituents = CH2CH3, CHzCF3, CH3, and C~H S ) .These complexes crystallize as infinite "crinkled" tapes having components joined by a triad of hydrogen bonds. The tapes are prevented from adopting a linear motif due to steric repulsion between tert-butyl groups on adjacent melamines; the crinkled motif avoids such repulsion. The tape backbones deviate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
85
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(90 citation statements)
references
References 0 publications
5
85
0
Order By: Relevance
“…Most of the examples reported to date focused on steric effects on metal coordination, [8] or on the secondary structures of coordination [9] or hydrogen-bonded solids. [10] Here we illustrate a clear example of steric control over the primary hydrogen bonding structures in crystalline N,N'-dialkylthioureas (Scheme 1). [11] We show that the steric bulk of the organic substituents on the thiourea group can be exploited to direct the formation of either chains or dimers, the two hydrogen bonding arrangements typically observed in this class of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the examples reported to date focused on steric effects on metal coordination, [8] or on the secondary structures of coordination [9] or hydrogen-bonded solids. [10] Here we illustrate a clear example of steric control over the primary hydrogen bonding structures in crystalline N,N'-dialkylthioureas (Scheme 1). [11] We show that the steric bulk of the organic substituents on the thiourea group can be exploited to direct the formation of either chains or dimers, the two hydrogen bonding arrangements typically observed in this class of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that barbiturates or cyanurates could self-assemble into highly organized structures such as linear tapes, crinkle tapes, or rosettes with complementary hydrogen-bonding melamines in the solid state or solution. [10][11][12][13][14][15][16][17][18] More recently, the formation of hydrogenbonding networks between these complementary components has also been investigated in 2-D at the air-water interface. 19,20 Traditionally, it was believed that hydrogen bonding directed molecular recognition is difficult in polar media, such as water, due to the competition from the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Such a system comprises most frequently the weak hydrogen bonds of N-H ÎO and O-HÎO types. [13][14][15][16][17][18][19][20][21][22][23] This phenomenon has a feature of self-organization process, widely reported in literature. The results obtained during analysis the structures of acetates can be used to discuss a design strategy for the engineering of crystals with predesigned architecture.…”
Section: Introductionmentioning
confidence: 99%
“…12,15,18,19,21,22,28,38,40,42,43 On the other hand, in some salts the melamine molecule is doubly protonated. 13,14,20,44 It is worthwhile to mention here the structure of 3-amino-1,2,4-triazine published by Perpétuo and Janczak. 41 In the context of literature data it seemed to be worthwhile to give the vibrational characterisation of crystalline melaminium acetate acetic acid solvate monohydrate in order to expand the understanding of the physical organic chemistry of the solid state containing multiple hydrogenbonding systems.…”
Section: Introductionmentioning
confidence: 99%